A novel intelligent ultra-local model control-based type-II fuzzy for frequency regulation of multi-microgrids. (March 2022) - Sohrabzadi, Erfan; Gheisarnejad, Meysam; Esfahani, Zahra; Khooban, Mohammad Hassan
Due to the random nature of renewable energy in the micro-grid (MG) configuration, the energy generators in such systems are not able to offer an uninterrupted power and a mismatch between the demand and generation will be occurred. To alleviate this unbalance, technically, conventional storage devices are one of the practical solutions to this issue. However, the implementation of storage system is not effective from the economic preceptive and, as an alternative, the battery of electric vehicle can be also embedded in the structure of the MGs. In this work, an ultra-local model (ULM) controller based on a single-interval type-II fuzzy logic (SIT2-FL) controller is applied for frequency regulation of multi-MG(s) with electric vehicles. In this scheme, the ULM controller plays a critical role in the reducing the dependency of the controller to the MG model. An extended observer error is embedded in the structure ULM controller to remove the uncertainties included in the system. The SIT2-FL is established as supplementary controller to remove the error of observer and further ameliorate the multi-MG performance. Comparative simulation analysis and robustness examination are made to ascertain the usefulness of the suggested ULM controller-based SIT-FL.